A Literature Review On Corporate Cash Holdings Decisions - Mouline, Boubker (The journal of contemporary issues in business and government, 2021)
There has been a growing interest in the issue of treasury and cash holdings as its purpose has overgone several important changes within companies over time. It has evolved from a simple function of comparing accounting and banking information to a function that is at the heart of the strategic sphere of the company. However, in spite of this growing interest, the phenomenon of holding cash has been the subject of rare research, yet to satisfy all the theoretical doubts and curiosity related to this subject. Based on theories explaining the liquidity-accumulating behavior of firms, this research reviews the role of different financial theories such as, trade off theory, pecking order theory and agency theory in the decision making of corporate cash management practices. Majority of the literature depicts the prominence of trade off theory and pecking order theory in the cash management practices of firms. However, some empirical and theoretical studies also described the significance of agency theory. Starting from the motivation of cash holding, this study warrants the need to empirically extent the significance of financial theories in the future.